Concept, essence, value of manuals and their difference from other types of material payments (Journal of actual problems of jurisprudence, 2019)
This is article were consider to the idea or essence or importance allowance and their difference for seconds kinds material payment.For all kinds of monetary payments which are called as grants, a number as the general sign is characteristic, allowing carrying them toone kind of social security — to grants, and a number of the signs establishing essential distinctions between separate kinds of grants.